Ultrathin single-crystal ZnO nanobelts : Ag-catalyzed growth and field emission property - Xing, G. Z. (2012)
We report the growth of ultrathin single-crystal ZnO nanobelts by using a Ag-catalyzed vapor transport method. Extensive transmission electron microscopy and atomic force microscopy